Directors as Guardians of Compliance and Ethics Within the Corporate Citadel What the Policy Community Should Know - Greenberg, Michael D. (RAND Corporation, 2010)
RAND convened a symposium on the perspective and role of corporate boards of directors in overseeing their firms' ethics and compliance matters. These conference proceedings summarize the event and the discussions, which focused on oversight challenges that directors face, board responsibility for corporate culture, and steps that business leaders and policymakers might take to better encourage and empower directors in their oversight role.